Karyological Investigation on Five Taxa of Bellevalia Lapeyr. (Asparagaceae) from Turkey - Dogan, Gulden; Kiran, Yasar; Paksoy, M. Yavuz (Univ Tokyo Cytologia, 2019)
The somatic chromosome numbers and karyotypes were examined in five Bellevalia taxa including two endemic species of B. chrisii and B. gracilis distributed in Turkey. The chromosome numbers were determined as 2n= 2x=8 in all studied taxa [B. chrisii Yildirim & B. Sahin sp. nov., B. glauca (Lindl.) Kunth., B. gracilis Feinbrun, B. longipes Post, B. sarmatica (Pallas ex Georgi) Woronow]. The karyotype formula was determined as 2m+sm+st in B. chrisii and B. longipes, 3m+st in B. glauca, B. gracilis and B. sarmatica. The findings for each of the analyzed taxa are compared with the results of previous studies.
Keywords: Asparagaceae; Bellevalia; Chromosome number; Karyotype; Turkey